2021
DOI: 10.47836/pjssh.29.s3.15
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Chinese Language Learning Strategies in the Past Decade (2011-2020)

Abstract: Empirical studies and literature on Chinese language learning strategies (CLLS) in China and abroad have outlined theoretical introductions and case descriptions for nearly a decade. Reportedly, studies on CLLS indicated the following characteristics: The study respondents were primarily international students in China gearing towards regionalisation, nationalisation, or localisation. Furthermore, the qualitative study method followed an empirical, comprehensive, and descriptive learning strategy, such as obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
2
0
Order By: Relevance
“…Bagheri & Bavali, 2020), 'other studies show that language learning strategies and English proficiency have been mainly researched in face-to-face higher education settings' and (Mizhe et al, 2021) several study limitations were identified (uneven regional studies, insufficient research samples, single research methods, and lack of theoretical paradigms in training learning strategies. According to (Almusharraf et al, 2021), there is a need to identify the relationship between learner characteristics and reported levels of language learning strategies and examine the influence that self-efficacy, instrumental motivation, effort and persistence, and preferences to analyze the language learning strategy needed.…”
Section: Introductionmentioning
confidence: 99%
“…Bagheri & Bavali, 2020), 'other studies show that language learning strategies and English proficiency have been mainly researched in face-to-face higher education settings' and (Mizhe et al, 2021) several study limitations were identified (uneven regional studies, insufficient research samples, single research methods, and lack of theoretical paradigms in training learning strategies. According to (Almusharraf et al, 2021), there is a need to identify the relationship between learner characteristics and reported levels of language learning strategies and examine the influence that self-efficacy, instrumental motivation, effort and persistence, and preferences to analyze the language learning strategy needed.…”
Section: Introductionmentioning
confidence: 99%